Traducteur : auteur ou guide ? Letters from an Other de Lise Gauvin au-delà du stéréotype - Warmuzińska-Rogóż, Joanna (Romanica Silesiana, 2021)
The article aims to present the particularities of the English translation of Lise Gauvin’s novel Lettres d’une autre by a Canadian feminist translator, Suzanne de LotbinièreHarwood. The purpose of the translation was to make the Quebec culture closer to the English speaking Canadians. Moreover, de Lotbinière-Harwood intended to emphasize feminist issues. Indubitably, such a project goes beyond the stereotypical function of translation as the translator herself is clearly visible in the text. The specificity of the de Lotbinière-Harwood’s translation encourages the reflection on the problematic border between a translation sensu stricto and a translation being at the same time some kind of explanation. The article seeks to answer to the following questions: is a literary translator “only” a transmitter of meanings invented by the author or a guide in the unknown world? Is he also a full-fledged author? In addition, the article considers how far a translator is allowed to be visible in a text, in particular, if he aims to explain culture.